Association of adverse childhood experiences with anemia in older Chinese: Guangzhou Biobank Cohort Study - Shao Yi He; Wei Sen Zhang; Chao Qiang Jiang; Ya Li Jin; Tai Hing Lam; Kar Keung Cheng; Lin Xu (Scientific Reports, 2024)
Abstract To examine the association of adverse childhood experiences (ACEs) with anemia among older people. 24,116 participants aged 50 years or above were recruited. Multivariable linear and logistic regression was used to assess the associations of self-reported ACEs number with hemoglobin concentrations (g/dL) and presence of anemia. Older individuals with two or more ACEs, versus no ACEs, showed lower hemoglobin concentrations (β =  − 0.08 g/dL, 95% confidence intervals (CI) − 0.12 to − 0.03) and higher odds of anemia (odds ratio = 1.26, 95% CI 1.01–1.59). A more pronounced association between ACEs and anemia in the lower education group was found, while the association became non-significant in those with higher education (P for ACEs-education interaction = 0.02). ACEs was associated with anemia in older people, and the association was stronger in those with lower education, highlighting the significance of early-life psychological stressors assessment and consideration of education background in geriatric care.